India. The Modi Factor - Nicola Missaglia (Pubblicazioni ISPI, 2018)
When Narendra Modi was elected Prime Minister of India in 2014, he promised to push through key reforms and bring about the massive economic development needed for the "world's largest democracy" to win its place among global superpowers. With over 1.3 billion citizens, India is soon to become the world's most populous country, and more than one quarter of the people joining global workforce during the next decade will be Indian. The poorest of the world's 20 largest economies, India's potential for catch-up growth is enormous. And so are the limits and contradictions India must overcome for Modi's vision to gain momentum. What has his government achieved so far? How likely is Modi's "Minimum government, maximum governance" strategy to deliver the expected outcomes? Is India, often described as a "reluctant superpower", now closer to becoming a regional leader? In a crucial year for local elections, and with the Prime Minister ready to run for a second term in 2019, this volume investigates the economic, political and diplomatic trajectories of Modi's India in its quest for a global role.